The role of the government internal control system (SPIP) in budget optimization in local governments in Indonesia - Ahmad, Imran; Furqan, Andi Chairil (Journal of Economics and Business Letters, 2025)
This study analyzes the role of SPIP, the internal control of Indonesia, within the broader framework of Public Financial Management (PFM) and how it influences the appropriation of health budgets to achieve Sustainable Development Goal 3 (SDG 3). In contrast to previous studies, which have predominantly focused on the coverage of health budgets, SPIP emerges, theoretically, as a moderating variable intervening between the relationship between expenditure on health and health results. Using JKN coverage, Indonesia's National Health Insurance program and chief tool for pursuing universal coverage for health, for tracking the realization of SDG 3, a dataset of 538 municipalities for a period of five years, from 2018 until 2022 (2,690 observations), the study conducts Moderated Regression Analysis using Generalized Least Squares, considering heteroscedasticity, as well as autocorrelation, for estimation. While the results confirm that a greater appropriation of the health budget promotes the success of JKN, whose impact is significantly boosted by SPIP due to the enhancement of transparency, accountability, and due utilization of the budget, evidence exists that points towards a strong internal control, when complemented with effective management of the budget, facilitating a catalyst towards SDG 3 realization. Furthermore, it provides impetus towards another motivation for policymakers to increase sustainability, along with greater inclusivity, for health developmental efforts, strengthen strategies for health budgeting, and realize SPIP implementation strategies.